Uptake of Single-Walled Carbon Nanotubes Conjugated with DNA by Microvascular Endothelial Cells - Joseph Harvey; Lifeng Dong; Kyoungtae Kim; Jacob Hayden; Jianjie Wang (Journal of Nanotechnology)
Single-walled carbon nanotubes (SWCNTs) have been proposed to have great therapeutic potential. SWCNTs conjugated with drugs or genes travel in the systemic circulation to reach target cells or tissues following extravasation from microvessels although the interaction between SWCNT conjugates and the microvascular endothelial cells (ECs) remains unknown. We hypothesized that SWCNT-DNA conjugates would be taken up by microvascular ECs and that this process would be facilitated by SWCNTs compared to facilitation by DNA alone. ECs were treated with various concentrations of SWCNT-DNA-FITC conjugates, and the uptake and intracellular distribution of these conjugates were determined by a confocal microscope imaging system followed by quantitative analysis of fluorescence intensity. The uptake of SWCNT-DNA-FITC conjugates (2 μg/mL) by microvascular ECs was significantly greater than that of DNA-FITC (2 μg/mL), observed at 6 hrs after treatment. For the intracellular distribution, SWCNT-DNA-FITC conjugates were detected in the nucleus of ECs, while DNA-FITC was restricted to the cytoplasm. The fluorescence intensity and distribution of SWCNTs were concentration and time independent. The findings demonstrate that SWCNTs facilitate DNA delivery into microvascular ECs, thus suggesting that SWCNTs serving as drug and gene vehicles have therapeutic potential.